MEASUREMENT OF W-PRODUCTION AND Z-PRODUCTION PROPERTIES AT THE CERN PBARP COLLIDER - Ansari, R; Bagnaia, P; Banner, M; Battiston, R; Bernlohr, K; Booth, C; Borer, K; Borghini, M; Carboni, G; Cavasinni, V; Cenci, P; Chollet, J; et al. (1987)
A study has been made of the production characteristics of W and Z bosons produced at the CERN pp Collider. The event sample consists of 251 W→ev decays, and 39 Z→e+e- decays, identified by the UA2 detector, and corresponds to an integrated luminosity of 142 nb-1 at √s = 546 GeV, and 768 nb-1 at √s = 630 GeV. Measurements of W and Z production cross sections, of longitudinal and transverse momentum distributions, and of associated jet production, are presented. These measurements are compared with theoretical expectations, which include higher order QCD effects. © 1987.